Superconducting 63-pole 2 Tesla wiggler for Canadian Light Source - Khruschev, S.V.; Kuper, E.A.; Lev, V.H.; Mezentsev, N.A.; Miginsky, E.G.; Repkov, V.V.; Shkaruba, B.A.; Syrovatin, V.M.; Tsukanov, V.M. (Вопросы атомной науки и техники, 2006)
A superconducting 63-pole wiggler with the average period 34 mm designed and fabricated at the Institute of
Nuclear Physics in Novosibirsk for Synchrotron Radiation Center (CLS) in Canada is described. The maximum field
2.2 Tesla in the median plane has been achieved. The liquid helium consumption less than 0.03 liters per hour in
operating mode has been reached. In January 2005, the wiggler was installed in the storage ring in CLS and now
experiments are already underway. The main parameters of the magnet and the cryogenic systems as well as test
results are presented. Описан 63-полюсный сверхпроводящий вигглер со средним периодом 34 мм, изготовленный в ИЯФ СО РАН для центра синхротронного излучения CLS в Канаде. Получено максимальное поле в медианной плоскости 2.2 Т. При этом расход жидкого гелия в рабочем режиме менее 0.03 литра в час. Вигглер установлен на накопительное кольцо CLS и ведутся эксперименты с СИ. Приведены основные параметры магнитной и криогенной систем. Описаний 63-полюсний надпровідний вігглер із середнім періодом 34 мм, виготовлений в ІЯФ СО РАН для центра синхротронного випромінювання CLS у Канаді. Отримано максимальне поле в медіанній площині 2.2 Т. При цьому витрата рідкого гелію в робочому режимі менш 0.03 літра в годину. Вігглер установлений на накопичувальне кільце CLS і ведуться експерименти із СІ. Наведено основні параметри магнітної й криогенної систем.